2017
DOI: 10.1016/j.jphotobiol.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low-level laser therapy on the healing of human bone maxillofacial defects: A systematic review

Abstract: Within the limitation of this review, a possible improvement in bone density can be found when LLLT is applied postoperatively in maxillofacial bony defects. LLLT also seems to promote anti-inflammatory and analgesic effects and accelerate healing, as well as enhance quality of life related to oral health. However, LLLT use protocols need to be standardized before more specific conclusions can be drawn about this subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 51 publications
(158 reference statements)
1
37
0
3
Order By: Relevance
“…This systematic review was conducted in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist, as well as previously published systematic reviews [43,44].…”
Section: Methodsmentioning
confidence: 99%
“…This systematic review was conducted in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist, as well as previously published systematic reviews [43,44].…”
Section: Methodsmentioning
confidence: 99%
“…Research in vitro has demonstrated that laser irradiation (LI) promotes cell migration and proliferation [14,15], mitochondrial respiration [16,17,18], protein synthesis [14,19] and bone formation [20]. Dental pulp stem cells (DPSCs) have a mesenchymal stem cell (MSC) phenotype, and the potential to differentiate into multiple cell types, including odontoblasts, osteoblasts, chondrocytes, cardiomyocytes, hepatocytes, neuron, liver cells, and pancreatic islet β cells.…”
Section: Introductionmentioning
confidence: 99%
“…Santinoni et al, in 2017, evaluated the efficacy of LLLT in the healing of maxillofacial bone defects. 54 They only reviewed randomized clinical trials in their systematic review. Studies on transverse maxillary expansion and maxillary cystic defects, one study on DO of the mandible, 37 and studies on cases after tooth-extraction, orthodontic tooth movement and periodontal defects were reviewed.…”
Section: Discussionmentioning
confidence: 99%